FRI0289 Role of cxcl13 and cxcl12 in sjogren's syndrome: association with histological, clinical and laboratory features. (12th June 2018) - Colafrancesco, S.; Priori, R.; Pipi, E.; Campos, J.; Nayar, S.; Cerbelli, B.; Arienzo, F.; Giordano, C.; Bombardieri, M.; Valesini, G.; Barone, F.
Abstract : Background: Ectopic production of the lymphoid chemokines CXCL13 and CXCL12 has been described in tertiary lymphoid structures (TLS) that harbour in the salivary glands of patients with Sjogren's Syndrome (pSS). Whilst CXCL13 expression correlates with clinical features, its potential role as a biomarker to monitor the organisation and severity of the salivary gland infiltrate has been hampered by the lack of sensitive tools to describe TLS extent and features. Objectives: To investigate CXCL13 and CXCL12 serum and tissue expression and to find any possible association with clinical, histological and laboratory features. Methods: We studied histological features of the minor salivary glands (MSG) and sera of respectively fifty and seventy (table 1) unselected consecutive patients with pSS (AECG criteria). Concentration of CXCL13 and CXCL12 were evaluated by ELISA in patient sera and eleven healthy controls (HC). Paraffin embedded MSG were studied by haematoxylin/eosin and anti-CD3, anti-CD20, anti-CD21 staining. Images analysis was used to calculate focus score (FS), mean foci area, percentage of infiltration (%i), segregated foci (%SF), %GCs and lymphoepitelial lesions (%LEL). GCs from MSG and tonsils were microdissected and quantitative PCR was used to test CXCL12 and CXCL13 transcripts. Results: Histological analysis unveiled strong correlations between the mean foci area with the%i and the presence of SF; positive correlations were also observed between the%i and both the FS and%SF. This was significantly higher in patients exhibiting SF. The% of SF positively correlated with FS, presence of%GC and%LEL that also correlated with the%i and the%SF (image). Mean CXCL13 and CXCL12 serum levels were significantly higher in pSS compared to HC [(124.12±119.73 pg/ml vs 8.9±15.4 pg/ml (p=0.001) and 34.6±54.2 pg/ml vs 2.5±8.3 pg/ml (p=0.05), respectively]. CXCL13 was significantly higher in patients with SF, with GCs and LEL and correlated with the mean foci area, the%i, the FS and the percentage of LEL. Higher CXCL13 levels were associated with the presence of antibodies and other biological findings including hyperglobulinemia. Higher CXCL13 levels were also able to discriminate patients with lymphoma (p=0.009). CXCL12 levels correlated with the FS, %i and% of LEL. Transcript analysis showed no difference in the expression of CXCL13 between MSG and tonsil GC, whilst CXCL12 was found significantly higher in MSG (p<0.0001). Conclusions: Our results suggest the utility to expand the parameters of histologic evaluation of MSG, whilst reinforcing the role of the FS as reliable instrument to reflect the severity of inflammation. Analysis of MSG infiltration and foci segregation was able to identify subjects with increased proliferative risk. We demonstrated that serum CXCL13, is a biomarker of histological severity and is able to stratify patients with lymphoma. The high levels of CXCL12 in MSG GC suggest a differential biology of TLS in the SG, probably implicated in aberrant B cell clone survival. Disclosure of Interest: None declared